Reverence Thru Cadaveric Oath: The Need of the Hour - Gaikwad, Manisha R. (New Frontiers in Medicine and Medical Research Vol. 5, 2021)
In today’s scenario the doctor –patient relationship is getting from bad to worse because of the lack of communication skills in undergraduate students pursuing medicine. Acquiring knowledge through dissection of human body is an age-old concept started in 15th century by barber surgeons to demonstrate the structure of human body. Students pursuing medical profession have Anatomy as one of the three basic pre-clinical subjects in there very first year of medical career. Importance of cadaveric dissection for learning anatomy helps the students in developing spatial and tactile appreciation of the structures which cannot be obtained by prosected specimens, computerized learning aids or any other virtual dissection tables. Cadaver being their first teacher, students should be imbibed with the moral values and have gratitude towards the cadaver for helping them understand the structures of the body through dissection. Cadaveric oath recitation will help the students in developing empathy with the cadaver as a “SILENT TEACHER” and in the long run with the patients while serving the humanity by way of medical practice.